The RING finger domain E3 ubiquitin ligases BRCA1 and the RNF20/RNF40 complex in global loss of the chromatin mark histone H2B monoubiquitination (H2Bub1) in cell line models and primary high-grade serous ovarian cancer. (25th October 2016) - Dickson, Kristie-Ann; Cole, Alexander J.; Gill, Anthony J.; Clarkson, Adele; Gard, Gregory B.; Chou, Angela; Kennedy, Catherine J.; Henderson, Beric R.; ,; Fereday, Sian; Traficante, Nadia; Alsop, Kathryn; et al.
Abstract: Enzymatic factors driving cancer-associated chromatin remodelling are of increasing interest as the role of the cancer epigenome in gene expression and DNA repair processes becomes elucidated. Monoubiquitination of histone H2B at lysine 120 (H2Bub1) is a central histone modification that functions in histone cross-talk, transcriptional elongation, DNA repair, maintaining centromeric chromatin and replication-dependent histone mRNA 3'-end processing, as well as being required for the differentiation of stem cells. The loss of global H2Bub1 is seen in a number of aggressive malignancies and has been linked to tumour progression and/or a poorer prognosis in some cancers. Here, we analyse a large cohort of high-grade serous ovarian cancers (HGSOC) and show loss of global H2Bub1 in 77% (313 of 407) of tumours. Loss of H2Bub1 was seen at all stages (I-IV) of HGSOC, indicating it is a relatively early epigenomic event in this aggressive malignancy. Manipulation of key H2Bub1 E3 ubiquitin ligases, RNF20, RNF40 and BRCA1, in ovarian cancer cell line models modulated H2Bub1 levels, indicative of the role of these RING finger ligases in monoubiquitination of H2Bub1 in vitro . However, in primary HGSOC, loss of RNF20 protein expression was identified in just 6% of tumours (26 of 424) and did not correlate with global H2Bub1 loss. Similarly, germline mutation of BRCA1 did not show a correlation with the global H2Bub1 loss. We conclude that the regulation of tumour-associated H2Bub1 levels is complex. Aberrant expression of alternative histone-associated 'writer' or 'eraser' enzymes are likely responsible for the global loss of H2Bub1 seen in HGSOC.